2022
DOI: 10.3390/cryst12060755
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity of Bitumen via WAXD and DSC and Its Effect on the Surface Microstructure

Abstract: It is well documented that most bituminous binders contain crystallisable material. This crystallisable fraction, often referred to as paraffinic or natural wax, is associated with the bitumen’s origin and has an influence on its rheological performance. In the literature, Differential Scanning Calorimetry (DSC) is the primary technique used to determine the melting and crystallisation behaviour of this waxy fraction. However, in bitumen, thermal transitions in DSC are typically very broad and can be combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…The wax content in asphalt is positively correlated with the integral area of the ordered-to-disordered phase transition region. This order–disorder phase transition of asphalt can be discussed by previous studies on DSC . Saturated hydrocarbons form an aggregative solid structural crystalline phase in accordance with the laws of structural phase transitions and the nucleation mechanism of thermodynamic phase separation.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The wax content in asphalt is positively correlated with the integral area of the ordered-to-disordered phase transition region. This order–disorder phase transition of asphalt can be discussed by previous studies on DSC . Saturated hydrocarbons form an aggregative solid structural crystalline phase in accordance with the laws of structural phase transitions and the nucleation mechanism of thermodynamic phase separation.…”
Section: Resultssupporting
confidence: 62%
“…This order− disorder phase transition of asphalt can be discussed by previous studies on DSC. 52 Saturated hydrocarbons form an aggregative solid structural crystalline phase in accordance with the laws of structural phase transitions and the nucleation mechanism of thermodynamic phase separation. Asphaltenes create over a relatively long-time aggregative solid structurally amorphous (liquid) phase as a result of relaxation structural glass transition by a spinodal thermodynamic phase separation mechanism.…”
Section: ■ Results and Discussionmentioning
confidence: 82%
“…Bitumen is a complex organic mixture of hydrocarbons and nonhydrocarbons, with relatively large molecular weight. In order to study the chemical composition of bitumen, people have carried out a lot of research work, including nuclear magnetic resonance (NMR), small-angle neutron scattering (SANS) and small-angle X-ray scattering (SAXS) [ 52 ]. However, due to the complex chemical composition and diverse sources of bitumen, the specific molecular formula of bitumen is still uncertain and divergent [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that washing processes changed the thermal characteristics of lignin samples [34]. Another important research area in the study of lignin-modified bitumen is the use of Differential Scanning Calorimetry (DSC) testing to evaluate its thermal properties, including the glass transition temperature (T g ) and degree of crystallinity [35,36]. The glass transition temperature (T g ) and degree of crystallinity are critical factors in assessing and determining the performance characteristics of bitumen [37].…”
Section: Lignin-modified Bitumenmentioning
confidence: 99%